2014
DOI: 10.1007/s10853-014-8703-4
|View full text |Cite
|
Sign up to set email alerts
|

Toughening of electrospun poly(l-lactic acid) nanofiber scaffolds with unidirectionally aligned halloysite nanotubes

Abstract: The mechanical properties of the tissue engineering scaffold are important as they are tightly related the regeneration of structural tissue. The application of poly(L-lactic acid) (PLLA) nanofiber scaffolds in tissue engineering has been hindered by their insufficient mechanical properties. In the study, halloysite nanotubes (HNTs) were used to reinforce the mechanical properties of PLLA-based nanofibers. 4 wt% HNT/PLLA nanofiber membranes possess the best mechanical performance, which represents 61 % increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
35
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 80 publications
(37 citation statements)
references
References 54 publications
(58 reference statements)
2
35
0
Order By: Relevance
“…It was found that the tensile strength and elongation at break of PE electrospun nanofiber membranes were improved by 57% and 36%, respectively, compared with neat PLA electrospun nanofiber membranes, which could be attributed to the incorporation of OA‐MIONs as emulsifier into PLA nanofibers. Nanofillers including MIONs nanoparticles have also been employed for mechanical enhancement of polymeric nanofibers . In this study, the application of OA‐MIONs not only contributed to producing the core/shell structure of nanofiber but also endowed the favorable antibacterial, superparamagnetic, and mechanical properties of polymeric nanofibers, which is expected to extend their applications in various fields such as tissue engineering and drug carriers.…”
Section: Resultsmentioning
confidence: 89%
“…It was found that the tensile strength and elongation at break of PE electrospun nanofiber membranes were improved by 57% and 36%, respectively, compared with neat PLA electrospun nanofiber membranes, which could be attributed to the incorporation of OA‐MIONs as emulsifier into PLA nanofibers. Nanofillers including MIONs nanoparticles have also been employed for mechanical enhancement of polymeric nanofibers . In this study, the application of OA‐MIONs not only contributed to producing the core/shell structure of nanofiber but also endowed the favorable antibacterial, superparamagnetic, and mechanical properties of polymeric nanofibers, which is expected to extend their applications in various fields such as tissue engineering and drug carriers.…”
Section: Resultsmentioning
confidence: 89%
“…It is known that nanoparticles (i.e., silica, hydroxyapatite, metal, metal oxides, and other inorganic particles), tubular materials (i.e., carbon nanotube and halloysite nanotubes) and layered materials (i.e., graphene derivatives and layered silicate) can improve the mechanical strength of electrospun nanofiber membranes . The effective mechanical enhancement does not work without efficient stress transfer from PEC nanofiber to nanofillers, which highly hinges on good dispersion and strong interactions between nanofillers and composite matrix . However, nanofillers agglomerate can accelerate crack initiation, impairing mechanical performance of composite nanofibers.…”
Section: Resultsmentioning
confidence: 99%
“…b that the maximum rate of nanofiber degradation decreased with increasing HNT content. Cai et al reported that the improvement of thermal stability through introducing fillers was largely dependent on the dispersion of fillers in matrix. Therefore, HNT nanotubes dispersed in PCL/Gel nanofibers creates a potential barrier to the passage of the volatile pyrolized products from the matrix, eventually retarding thermal decomposition of the modified nanofibers.…”
Section: Resultsmentioning
confidence: 99%